2015
DOI: 10.1007/s12223-015-0384-0
|View full text |Cite
|
Sign up to set email alerts
|

Limit of detection of genomic DNA by conventional PCR for estimating the load of Staphylococcus aureus and Escherichia coli associated with bovine mastitis

Abstract: Detection of mastitis-associated bacteria can be accomplished by culturing or by molecular techniques. On the other hand, rapid and inexpensive methods to enumerate bacterial load without culturing can be better achieved by molecular methods. Staphylococcus aureus and Escherichia coli are the predominant bacterial pathogens associated with bovine mastitis. Here, we describe the application of conventional PCR for the limit of detection (LOD) of genomic DNA of S. aureus and E. coli based on single-copy genes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Lanes 3, 7, and 11 were biofunctionalized samples subjected to a higher antibody immobilization time (out of standardized conditions) and they were negative to PCR validation. Considering that the sensitivity of a conventional PCR ranges from 0.45 to 194 DNA pg, 44 the obtained genomic DNA was not enough for positive PCR validation. This could have resulted in the blockage of antibody active sites for bacterial epitope recognition confirming that bacteria are unable to bind superficially.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Lanes 3, 7, and 11 were biofunctionalized samples subjected to a higher antibody immobilization time (out of standardized conditions) and they were negative to PCR validation. Considering that the sensitivity of a conventional PCR ranges from 0.45 to 194 DNA pg, 44 the obtained genomic DNA was not enough for positive PCR validation. This could have resulted in the blockage of antibody active sites for bacterial epitope recognition confirming that bacteria are unable to bind superficially.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nonetheless, similar studies have found comparable results, whereby metabarcoding using the Illumina platform identi ed more pathogen positive samples than cPCR with Sanger sequencing (31,75,76). Such ndings may represent a diagnostic limit of detection for cPCR as samples can only be Sanger sequenced successfully upon ampli cation and visualisation of a PCR product band, with such bands only observable above a certain threshold concentration of DNA (77)(78)(79). This threshold concentration may be much lower or non-existent for deep sequencing methodologies which can successfully amplify from PCR product, even if no such product is visualisable on a gel (80).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, targeting a gene which is carried in known number of copies by all the members of a population is critical. We chose three genes for each of these organisms as it was possible that the LOD could be better with one than with the others (Chandrashekar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Here single copy genes, nuc for Staph. aureus and uidA for E. coli were selected based on its minimum detection limit as mentioned by Chandrashekar et al (2015).…”
Section: Introductionmentioning
confidence: 99%